Gambaran Penerapan Hazard Analisys Critical Control Point (HACCP) Pada Pembuatan Tahu di Home Industri Tahu MD Kampung Sawah Kecamatan Lubuk Basung - Lindawati, Lindawati; Husna, Ainul; Riviwanto, Muchsin` (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Padang, 2022)
Abstract Tofu is a food product in the form of soft solids made through the process of processing glycine-type soybeans by depositing protein, with or without the addition of other permitted ingredients. The problems found were during the soaking of soybeans, the water used was cloudy and workers smoked during the tofu printing process. The tofu making process requires the HACCP system to be implemented to be able to control the danger points in each tofu making process. This type of research is descriptive which was carried out at the Home Industri Tahu MD Kampung Sawah, Lubuk Basung District. This research was carried out in December 2021 – Juni 2022 with the research subjects including workers, materials and tools and the object of research includes the tofu making process. The data collection techniques carried out are observations and interviews and are analyzed univariately. The results showed that the hazard analysis in making tofu includes physical, chemical and biological hazards with the most risk categories, namely high contained in the process of cooking, filtering, clumping and printing tofu. Critical control points (TKK) are obtained in 3 tofu making processes, namely the filtering process, clumping and tofu printing. Critical Limits include the absence of sweat splash contamination by workers, workers no longer smoking which can cause the entry of cigarette ash into tofu juice and the use of vinegar acid (CaSO4) according to dosage and needs. Based on the results of the study, it is hoped that the management of the Home Industry knows MD to hold training on the application of HACCP to workers so that workers know and can minimize what dangers can arise during the tofu making process. Keyword : HACCP; Tofu Making; and Home Industry